Climate Smart Mechanization in Central Asia - Devkota Wasti, Mina Kumari (International Center for Agricultural Research in the Dry Areas, 2022)
Drought and water scarcity have been a critical concern that threatens both food security and the economy globally as well as in Central Asia. Also, climate change is estimated to increase the drought risk in the region. The agricultural sector is vital for addressing the challenges in combating food insecurity, reducing poverty, enabling recovery from the pandemic (like COVID-19), and building resilience. Sustainable and efficient agricultural techniques that optimize land and water usage and help grow and produce more food can contribute to tackling these threats,and catalyze the transformative change of agri-food systems towards greener, inclusive and sustainable development. Scale-appropriate agricultural mechanization is crucial in supporting recovery and building resilience of farming communities to current and future shocks. Adoption of suitable machinery can increase food production, minimize water usage for irrigation, reduce production costs and post-harvest losses, as well as save manpower while also contributing to the reduction in carbon emissions. Thus, the identification, introduction, and scaling up of sustainable climate-smart mechanization practices is important for sustainable agriculture production in the region. This presentation highlights the different climate-smart mechanization options and their benefits for improving crop productivity while reducing production costs applicable to Central Asia.